2014
DOI: 10.1021/cr4000946
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging of Organic C-Centered Radicals by Nitroxides

Abstract: International audienceWOS:00033607820001

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 241 publications
5
96
0
Order By: Relevance
“…This is because of the limitations of cell imaging techniques, including low selectivity and sensitivity, and the need for very complicated instrumentation. However, recent reports have described profluorescence nitroxides that rely on features of nitroxides, such as stable unpaired electrons, very efficient carbon-centered radical spin trapping 6 and the ability to function as fluorescence switching molecules 7 . Indeed, profluorescence nitroxides have been used to detect carbon-centered radicals generated by enzymatic and nonenzymatic processes 8,9 .…”
mentioning
confidence: 99%
“…This is because of the limitations of cell imaging techniques, including low selectivity and sensitivity, and the need for very complicated instrumentation. However, recent reports have described profluorescence nitroxides that rely on features of nitroxides, such as stable unpaired electrons, very efficient carbon-centered radical spin trapping 6 and the ability to function as fluorescence switching molecules 7 . Indeed, profluorescence nitroxides have been used to detect carbon-centered radicals generated by enzymatic and nonenzymatic processes 8,9 .…”
mentioning
confidence: 99%
“…This result also indicated that the catalytic turnover might be suspended in the absence of TEMPO. TEMPO + ( 2 + ) lacked catalytic efficiency (Table , entry 7) …”
Section: Methodsmentioning
confidence: 99%
“…It has been proposed that the HAT event can be described by three different processes, which are not the topics of this review (Bagryanskaya & Marque, 2014).…”
Section: Kinetics Of Bioreductionmentioning
confidence: 99%